Estudio comparativo de recuperación de plata; mediante hidróxido de sodio, hipoclorito de sodio y dicromato de potasio a partir de placas radiográficas - De La Cruz Bustamante, Edgar Alexander (2017)
Considering the bibliographical information, in which it is mentioned that the printing negatives have deposited silver salt in colloidal form, it was proposed, and it was decided to execute an experimental project, consisting of recovering silver contained in the radiographic plates following 3 Comparative methods, and see which methodology has the highest extraction, evaluated and compared. In the first method, the silver salts of the plates were attacked with an aqueous solution of sodium hydroxide, allowed to react, and then neutralized with a solution of hydrochloric acid, forming silver chloride which separated. In the second method, the silver salts of the plates were attacked with sodium hypochlorite (commercial bleach), where they were allowed to react and the silver salts were converted to silver chloride which precipitated and separated. In the third method, the plates were attacked with potassium dichromate, allowed to react and adding nitric acid, where the silver salts were converted to silver chromate. The following experimental activity for the three methods consisted of a filtration so that silver chloride (AgCl) and silver chromate (Ag2CrO4) remained in the qualitative role. And so by adding the samples in crucibles to dry the sample in a stove, then placed in a crucible and added a flux or flux mixture (litharge, borax, common flour and sodium bicarbonate) to proceed to melt it at approximately 960 ° C, Leaving the regula (button of lead and silver), then to carry out the process of copelation at approximately 980 ° C for one hour, thus obtaining a bullón of pure silver. Finally, it was analyzed whether there was pure silver in the residual solutions, adding lead in powder and dilute hydrochloric acid, to heat it, and to follow the processes of filtration, drying, casting and copelation. At the end of the experimental procedure was the first method of sodium hydroxide (sodium hydroxide solution 4 M and a solution of hydrochloric acid with 80% purity) by having a higher% recovery of silver (98.3879%) with a silver law Of 5.4113 gr silver / kg radiographic plates and with a time of 260 min. Pure silver was also obtained in the residual solutions, where the solution of the 3rd method (5% nitric acid and 5% potassium dichromate) was the best grade (0.0876 gr / liters of solution), with respect to the others with a Time of 195 min. Subsequently the washed plates were rinsed with water for later use. This project was carried out on a micro scale in which the materials used were of dail use